2023
DOI: 10.1111/bjh.18823
|View full text |Cite
|
Sign up to set email alerts
|

COVID‐19 infection in patients with haematological malignancies: A single‐centre survey in the latest Omicron wave in China

Abstract: Coronavirus disease 19 , caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), was declared a pandemic by the World Health Organization (WHO) in March 2020. Later in November 2021, the Omicron variant with enhanced immune escape was first reported from Botswana and thereafter from South Africa with an increased infection. 1,2 The SARS-CoV-2 Omicron BF.7 (BA.5.2.1.7), a subvariant of BA.5, has been responsible for the ongoing resurgence of cases since late September 2022 in China. 3,4 The muta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
10
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 35 publications
5
10
0
1
Order By: Relevance
“…In our study, more severe/critical (4/42, 9.5% vs. 5.5% overall) COVID‐19 cases were observed in patients with comorbidities (≥1). Similar findings were reported by Duléry 16 and Zhu et al 14 . Together with our data, these findings highlight that more attention should be paid to elderly lymphoma patients and frail patients with comorbidities diagnosed with COVID‐19 in registered clinical trials.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…In our study, more severe/critical (4/42, 9.5% vs. 5.5% overall) COVID‐19 cases were observed in patients with comorbidities (≥1). Similar findings were reported by Duléry 16 and Zhu et al 14 . Together with our data, these findings highlight that more attention should be paid to elderly lymphoma patients and frail patients with comorbidities diagnosed with COVID‐19 in registered clinical trials.…”
Section: Discussionsupporting
confidence: 92%
“…We selected the severity of COVID‐19 as the primary outcome in this study, and three significant risk factors were identified, including age ≥70 years, comorbidities, and PI3Ki‐containing regimens. Most previous studies 14,16,21 have revealed that elderly HM patients were more likely to have unfavorable outcomes of COVID‐19, including severe/critical illness, prolonged in‐hospital stay, and death. In our study, more severe/critical (4/42, 9.5% vs. 5.5% overall) COVID‐19 cases were observed in patients with comorbidities (≥1).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Omicron's hospitalization rate and mortality rate decreased significantly in the immunocompetent population, 2,3 it remains a fatal threat to patients with immunocompromised hematological malignancies (HM). 4 The overall mortality rate of Omicron infection was 16.5% among hospitalized HM patients according to the "EPICOV-IDEHA survey report," 5 significantly higher than that observed in the general population. [6][7][8] Additionally, new immune-evading subvariants of Omicron continue to emerge, 9,10 increasing the risk of reinfection.…”
mentioning
confidence: 99%